Distributed composite output consensus protocols of higher-order multi-agent systems subject to mismatched disturbances - Li, Guipu; Wang, Xiangyu; Li, Shihua (IET control theory & applications, 2017)
In the existing literatures, most of the anti-disturbance consensus control methods focus on multi-agent systems with slow time-varying matched disturbances. In practise, the multi-agent systems are usually subject to mismatched disturbances and the disturbances are usually fast time-varying. This study investigates the output consensus problem of higher-order multi-agent systems with mismatched disturbances, which are allowed to be fast time-varying. Firstly, to estimate the matched disturbances, mismatched disturbances and their higher-order derivatives, a generalised proportional–integral observer is constructed for each agent. Secondly, by distributedly employing the estimates of the mismatched disturbances and their higher-order derivatives, for both leaderless and leader–follower cases, two kinds of non-linear sliding-mode surfaces are developed, respectively. Thirdly, with the designed surfaces and the disturbances estimation information, feedforward–feedback composite consensus protocols are designed for both cases, which guarantee asymptotical consensus of the agents' outputs. Simulation results show the effectiveness of the proposed consensus algorithms.